Analisis Keuangan Pelaku UMKM Berbasis Local Wisdom Di Kota Palangka Raya - Benius Benius; Rossy Naptania; Lala Lala; Mika Taradiva; Rahmah Norhayati; Arum Widiya (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research presents a thorough analysis of the financial aspects influencing the performance of Micro, Small, and Medium Enterprises (MSMEs) based on local wisdom in their operational activities. Through a case study approach, financial ratio analysis, and survey, we explore the financial performance faced by locally based MSMEs. The implications of this research are significant for the government, business actors, and society in supporting the growth and sustainability of locally based MSMEs, as well as providing guidance for more effective policies to support this sector. Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the national and local economy, determined by criteria such as net worth, annual sales, and number of employees. Financial analysis of locally based MSMEs explores the financial aspects of micro, small, and medium enterprises (MSMEs) relying on local wisdom in their operations. This research aims to understand the financial performance, challenges, and opportunities faced by locally based MSMEs. The analysis methods used include quantitative descriptive with calculations of profitability ratios and activity ratios to gain comprehensive understanding. The results of this research are expected to provide insights for stakeholders, including the government, business actors, and society, in supporting the growth and sustainability of locally based MSMEs.